2007
DOI: 10.2217/14622416.8.11.1545
|View full text |Cite
|
Sign up to set email alerts
|

Allelic Variants in the CYP2C9 and VKORC1 Loci and Interindividual Variability in the Anticoagulant Dose Effect Of Warfarin in Italians

Abstract: Our results clearly indicate VKORC1 as the gene with the largest contribution to MWWD. Analyzing only one tag SNP of VKORC1 gene (1173C>T), it is possible to foresee 20% of the total variability. Our results may contribute to give useful indications for clinicians especially in the initiation of therapy so as to avoid the risk of adverse events.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
41
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(48 citation statements)
references
References 22 publications
6
41
1
Order By: Relevance
“…Genetic analyses for CYP2C9 (*2 and *3 alleles) and VKORC1 correlated with INR and plasma R-and S-warfarin concentrations. The mean warfarin daily dose requirement was highest in patients with the allelic variant CYP2C9 *1/*1 compared with those with the variant *2 and *3 alleles and highest 64 Gage et al, 65 Bodin et al, 66 Voora et al, 67 Hillman et al, 68 Kimura et al, 69 Loebstein et al, 39 and Borgiani et al 50 reported similar findings when genotypes were distributed by race. Studies articulating combined CYP2C9 and VKORC1 allelic frequencies and associated warfarin doses are summarized in Table 5.…”
Section: Effect Of Allelic Variants On Warfarin Activitymentioning
confidence: 82%
“…Genetic analyses for CYP2C9 (*2 and *3 alleles) and VKORC1 correlated with INR and plasma R-and S-warfarin concentrations. The mean warfarin daily dose requirement was highest in patients with the allelic variant CYP2C9 *1/*1 compared with those with the variant *2 and *3 alleles and highest 64 Gage et al, 65 Bodin et al, 66 Voora et al, 67 Hillman et al, 68 Kimura et al, 69 Loebstein et al, 39 and Borgiani et al 50 reported similar findings when genotypes were distributed by race. Studies articulating combined CYP2C9 and VKORC1 allelic frequencies and associated warfarin doses are summarized in Table 5.…”
Section: Effect Of Allelic Variants On Warfarin Activitymentioning
confidence: 82%
“…The anticoagulant effects of warfarin are modifi ed also by diet and foods containing vitamin K, although the dietary infl uences tend to be of more short-term character (25). VKORC1*3 haplotype (3730G>A, rs7294) was also defi ned and is present in 38 % of Europeans (13). It causes an increase in the dosage of warfarin (AA) up to 30 % compared with WT (7).…”
Section: Discussionmentioning
confidence: 99%
“…In the early stages of therapy, PM phenotypes are at risk of increased bleeding after warfarin treatment. These individuals require lower doses of warfarin to achieve the desired anticoagulant effect compared to patients with at least one CYP2C9*1 (WT) haplotype (13). The enzyme activity is reduced to 12 % (CYP2C9*2) and 5 % (CYP2C9*3), respectively to WT (14).…”
mentioning
confidence: 99%
“…However, these values include uncertainties due to bias or imprecision in calculating them from incomplete data and also because of the inherent variability. Reported clinical PK parameters are subject to both inter-and intrastudy variability, which stems from different sources such as ethnicity; genetic variation in cytochrome P450 metabolizing enzymes (Tucker, 1994) such as CYP2D6 (Dorne et al, 2002;Abduljalil et al, 2010;Thompson et al, 2011), CYP2C9 (Loebstein et al, 2001;Borgiani et al, 2007), and CYP2C19 (Dorne et al, 2003;Crettol et al, 2005); comedication; health status; different assay and analysis; environmental factors; and clinical settings of the study such as sample size.…”
Section: Introductionmentioning
confidence: 99%